Recent progress on multidimensional construction of helicenes - Lin, Wei-Bin; Li, Meng; Fang, Lei; Chen, Chuan-Feng (Chinese chemical letters, 2018)
Helicenes have attracted more and more attention in the field of photoelectric materials and asymmetric catalysis for their unique Tr-conjugated screw-shaped structures and excellent chiroptical properties. However, further study and application of helicenes are based on novel idea, delicate design, and efficient synthetic methods Recent development of helicenes has witness various smart designs and approaches. In order to obtain a systematical and vivid introduction of latest development of helicenes, the idea of multidimensional construction is proposed in this review, which concludes the construction of multi- dimensions from length, extent, and height. We hope that this idea could be helpful to forecast the trend of helicene chemistry and provide the design inspiration of novel helicenes.